Incidence of Medication Errors in King Fahad Hospital Madina Saudi Arabia - Yaser Masuod Alahmadi; Majed Abdurhman Alharbi; Abdulaziz Jafar Almusallam; Rafif Yaser Alahmadi; Sultan Othman Alolayan (Universidade de São Paulo, 2023)
Abstract This study aimed to evaluate the incidence of medication errors over a period of one year in King Fahad Hospital Madina Saudi Arabia. This retrospective, cross-sectional study was conducted over a period of one year from 2018 January to 2018 December using patient's records. King Fahad Hospital in Madina was selected for the study center. Data collected include the number and types of errors, severity, location of errors, errors by profession, and errors occurred in the medical wards. Statistical analysis was carried out using statistical package for social science version22. A total of twenty- six hundred and fifty-eight medication errors were reported during the study period. Among the reports 2567(96.5%) of the errors were due to near misses, followed by transcribing errors 1597(60%), ordering errors 928(34.9%), duplicative therapy 765(28.7%), wrong dose 454(%). The most common procedures involve medication errors were wrong documentation 442(16.6%), duration 168(6.3%) wrong quantity 162(6.4%). Majority of the medication errors were contributed by physicians (99.2%) and 0.7% of them were due to the pharmacist. In conclusion study findings reported that yet some kind of medication errors has been under reported and it was common in most hospital, further studies with intervention programs needed to control the incidence of medication errors in a Saudi hospital.